Recombinant Atrial Natriuretic Peptide Prevents Aberrant Ca(2+) Leakage through the Ryanodine Receptor by Suppressing Mitochondrial Reactive Oxygen Species Production Induced by Isoproterenol in Failing Cardiomyocytes - Murakami, Wakako (PLoS One, 2016)
Catecholamines induce intracellular reactive oxygen species (ROS), thus enhancing diastolic Ca(2+) leakage through the ryanodine receptor during heart failure (HF). However, little is known regarding the effect of atrial natriuretic peptide (ANP) on ROS generation and Ca(2+) handling in failing cardiomyocytes. The aim of the present study was to clarify the mechanism by which an exogenous ANP exerts cardioprotective effects during HF. Cardiomyocytes were isolated from the left ventricles of a canine tachycardia-induced HF model and sham-operated vehicle controls. The degree of mitochondrial oxidized DNA was evaluated by double immunohistochemical (IHC) staining using an anti-VDAC antibody for the mitochondria and an anti-8-hydroxy-2′-deoxyguanosine antibody for oxidized DNA. The effect of ANP on ROS was investigated using 2,7-dichlorofluorescin diacetate, diastolic Ca(2+) sparks assessed by confocal microscopy using Fluo 4-AM, and the survival rate of myocytes after 48 h. The double IHC study revealed that isoproterenol (ISO) markedly increased oxidized DNA in the mitochondria in HF and that the ISO-induced DNA damage was markedly inhibited by the co-presence of ANP. ROS production and Ca(2+) spark frequency (CaSF) were increased in HF compared to normal controls, and were further increased in the presence of ISO. Notably, ANP significantly suppressed both ISO-induced ROS and CaSF without changing sarcoplasmic reticulum Ca(2+) content in HF (p<0.01, respectively). The survival rate after 48 h in HF was significantly decreased in the presence of ISO compared with baseline (p<0.01), whereas it was significantly improved by the co-presence of ANP (p<0.01). Together, our results suggest that ANP strongly suppresses ISO-induced mitochondrial ROS generation, which might correct aberrant diastolic Ca(2+) sparks, eventually contributing to the improvement of cardiomyocyte survival in HF.